Patient satisfaction as an indicator of service quality in malaysian public hospitals - Abd. Manaf, Noor Hazilah; Phang, Siew Nooi (Emerald, 2009)
The main aim of the paper is to provide an empirical analysis on patient satisfaction as an indicator of service quality in Malaysian public hospitals. Self‐administered questionnaires were administered to patients by convenience sampling. Two sets of questionnaires were used, one for inpatient and another one set for outpatient. Selection of hospitals was made according to states in Peninsular Malaysia. 23 hospitals covering all state level hospitals, the National Referral Centre and selected district hospitals were chosen as respondent hospitals. Two dimensions of service quality emerged, namely clinical and physical dimension of service. Both outpatient and inpatient were found to be more satisfied with clinical dimension of service than physical dimension. For outpatient satisfaction, there was positive correlation between waiting time and patient satisfaction. Patient satisfaction was also found to be higher in the smaller district hospitals than in the larger state hospitals. For clinical dimension of service, patients were satisfied with the services of doctors and nurses, while for physical dimension of service, patients were satisfied with the cleanliness of the facilities. The ability of the research to be conducted by random sampling was inhibited by the reluctance of patients to cooperate, which led to the use of convenience sampling. Studies have also shown that patients are reluctant to express their feelings on services provided by their caregivers. The study provides primary data for a nationwide study on patient satisfaction in Malaysian public hospitals, for both inpatient and outpatient.